Self Governance Community: Pendidikan Komunitas dalam Strategi Perjuangan Persatuan Waria Tegal - Ikhda Nurnoviyati (La-Tahzan: Jurnal Pendidikan Islam, 2019)
Word of Waria tend to negative conotation in the middle of society. Stereotipe of waria that is about life style which oppose against social norm. During the time, our society majority only seeing waria as abnormal idea. As a result, waria as a group and also individual find difficulties in accessing service of public and social relationship. Tegal Regency owning community of Waria which organized, named Persatuan Waria Tegal (PWT). PWT focused activity especially in health service and also the potency had by waria becoming member of PWT. To reach the target, PWT conduct Self Governing Community . This research aim to to know how PWT conduct Self Governance Community By education in community to build social relationship with society and state. Result of research of that PWT have conducted Self Governance Community good enoughly. The next step to develop;build existence by constructing social relationship with society and also government of Tegal Regency.